Nomegestrol acetate/17-beta estradiol: a review of efficacy, safety, and patient acceptability - Akintomide H; Panicker S (Dove Medical Press, 2015)
Hannat Akintomide, Sabeena Panicker Sexual and Reproductive Health, Central and North West London NHS Trust, Margaret Pyke Centre, London, UK Abstract: Nomegestrol acetate (NOMAC) 2.5 mg with 17-beta estradiol (E2) 1.5 mg is a new combined oral contraceptive (COC) formulation and is the first monophasic E2 pill to be marketed, having been licensed for use in Europe in 2011. It is available to be taken daily in a regimen of 24 active pills followed by four placebo pills. NOMAC is a highly selective 19-nor progestogen derivative with specific binding to progesterone receptors, anti-estrogenic activity and no androgenic, mineralocorticoid nor glucocorticoid effects. E2 is an estrogen that is identical to endogenous estrogen. While it has been in use for only a short period of time, current evidence suggests that NOMAC/E2 is just as effective, safe, and acceptable as existing COC preparations. Two large Phase III trials conducted in the Americas and across Europe, Australia, and Asia showed lower cumulative pregnancy rates in the NOMAC/E2 groups compared to the drospirenone (DRSP) 3 mg in combination with ethinyl estradiol (EE) 30 µg (DRSP/EE) groups but this difference was not statistically significant. NOMAC/E2 exhibits a good safety profile and has less effects on cardiovascular risk, hemostatic, metabolic, and endocrine factors in comparison to COCs containing EE in combination with levonorgestrel (LNG) or DRSP. NOMAC/E2 has also been found to cause less breast cell proliferation when compared to E2 alone and has some anti-proliferative effect on human breast cancer cells. NOMAC/E2 is considered acceptable as its compliance, continuation rates, and bleeding patterns were similar to COCs containing DRSP/EE and LNG 150 µg combined with EE 30 µg or LNG 100 µg combined with EE 20 µg (LNG/EE). However, discontinuation was found to be slightly higher in the NOMAC/E2 groups in the two large Phase III trials comparing NOMAC/E2 use with DRSP/EE. As the scientific literature has limited information on NOMAC/E2, further experience with NOMAC/E2 is required. Keywords: nomegestrol acetate, estradiol, efficacy, safety, acceptability